An allocative method of hybrid electrical and thermal energy storage capacity for load shifting based on seasonal difference in district energy planning. (15th September 2020) - Yan, Zhe; Zhang, Yongming; Liang, Runqi; Jin, Wenrui
Abstract: The power generation of renewable energy represented by wind and solar energy on energy supply-side has uncertainty. Meanwhile, the fluctuation problems in power system is also caused by increasing number of air-conditioning loads on energy demanded-side. For addressing the fluctuation, energy storage technology is considered as a crucial solution. Energy storage technology can also improve the flexibility of the power system and reduce the peak-valley difference. However, a large scale of electrical energy storage has less economic. Hybrid energy (including electrical and thermal energy) storage can be seen as a practicable solution instead of electrical energy storage. An allocative method of hybrid energy storage capacity is proposed in this paper. By use of this method, the mathematical model is explored between hybrid energy storage capacity and peak-valley difference. It is convenient to determine the capacity of hybrid energy storage depending on peak valley difference required. Moreover, seasonal difference of electrical load can determine the capacity of electrical and thermal energy storage, respectively. In addition, the economy model of energy storage capacity helps to find out the optimal capacity. This proposed method can be used as an analysis tool of district energy planning and energy system renewal. Highlights: An allocative method of hybrid energy storage capacity in district planning is proposed. This proposed allocative method contributes to the coordination of electrical and thermal energy storage. Seasonal difference of electrical load can determine the capacity of electrical and thermal energy storage. The optimal capacity can be calculated by establishing the economy model of energy storage. This method can be served as a tool of district energy planning and energy system renewal.